(untitled) (Revista Nacional de Odontología, 2014)
The elderly are exposed to multiple risk factors involving not only general health but also oral health, which can also notably affect their quality of life, well-being and integrity. The literature shows how this population is more susceptible to systemic conditions associated with oral cavity manifestations, as well as periodontal disease and cavities, to the point of causing tooth loss, a risk that increases with age. This bibliographical review takes into account information beginning in 2001. It includes studies made on the elderly, in which a relationship is established between quality-of-life and oral health.